Dividend Policy, Share Price and Future Profitability: Case of Commercial Banks in Nepal - Dhakal, Nabia; Shah, Ajay (Journal of Business and Social Sciences Research, 2018)
The study analyzes the impact of dividend policy on share price and future profitability of commercial banks in Nepal. Using panel secondary data of 13 commercial banks from year 2001 to 2014, correlation and regression analysis are applied for the study. The impact of dividend policy on share price is analysed first and the findings of initial analysis suggests that dividend yield and retention ratio have significant negative impact, whereas earning per share has significant positive impact on share price. The study, thus, supports the dividend relevance in Nepalese capital market, and it is further extended to analyze whether dividend changes carried any special information influencing future profitability of commercial banks in two subsequent year of dividend declaration. The conclusion from the analysis indicates that the current year dividend change has significant impact on current year earning changes. For subsequent years, the impact of dividend change is insignificant. Thus, dividend change does not carry information regarding changes in earning in subsequent years of dividend declaration and does not support signalling hypothesis in Nepalese capital market. Journal of Business and Social Sciences Research, Vol. 1, Issue 1, pp. 89-110